Improved commitment in educational search for meaning - Elena Madrussan (University of Bologna, 2015)
The pedagogical perspective of relationism has been developed in Italy by Enzo Paci, between the end of the Fifties and the Sixties of Twentieth century. It has influenced some of the most interesting developments of the next philosophical-educational reflection so that it remains, still today, a significant source of pedagogical question, especially concerning its methodological structure and the ethical commitment.A such ethically oriented idea of education has tasks that seems to be very topical: to safeguard the freedom of culture against the subjection to the reproduction of cultural models and the drifts of specialization; to respond to the social demand for a less partly, fragmented and utilitarian comprehension of reality; to decode the relationship's knots, which permeate subjective and collective existences, by standing again on their meaning, on their genesis, on their outcomes. From this picture emerge some significant alternatives of educational experience as practice of relationship between subject and world.